NMR in rapidly rotated metals - Tiffen, R. S. (1975)
Although this thesis is concerned solely with nuclear magnetic resonance, it may be divided into two parts. One part deals with a series of measurements on the NMR parameters of several pure metal powders, namely aluminium, cadmium, niobium and vanadium, and in particular the effect on their resonance spectra of rapid macroscopic sample rotation at the 'magic angle'. The other part relates measurements of spin-lattice relaxation time as a function of temperature for the three solid cuprous halides. By spinning at high speeds a significant narrowing of the resonance lineshape has been achieved in the case of cadium and aluminium. This has enabled precise determinations of their isotropic Knight shifts to be made. For cadmium the width of the residual symmetric central spectrum has been used to obtain an estimate of the magnitude of the indirect electron coupled exchange interaction. Complete narrowing of the aluminium resonance line requires rotation rates in excess of 8 kHz. To this end it has been necessary to develop a new rotor system capable of carrying small metal samples at extremely high spinning rates. In connection with the work on aluminium, pure powder specimens have been prepared which exhibit values of second moment and dipolar relaxation time that agree well with theory. This is in contradiction to the results obtained from filed powders and those recorded by all other workers. Below room temperature the form of the T1 results obtained from the cuprous halides is in accord with the theory of Raman quadrupole relaxation. However theoretical T1 values, as derived from the simple Raman two-phonon mechanism in an ionic crystal lattice, fail to give quantitative agreement with experiment.